Time-domain analysis of piezoelectric impedance-based structural health monitoring using multilevel wavelet decomposition - Vieira Filho, Jozué [UNESP]; Baptista, Fabricio Guimaraes [UNESP]; Inman, Daniel J. (Academic Press Ltd Elsevier B.V. Ltd, 2011)
A new approach to analyze the response from a piezoelectric wafer in an impedance-based structural health monitoring (SHM) method is proposed. It is shown that the time-domain response of a piezoceramic wafer provides information on the electromechanical impedance (EMI) variation when a monitored structure is damaged. Practical analysis was carried out using wavelet transform in two different levels. This approach simplifies EMI based SHM and the results show that it is more sensitive to damage than methods based on impedance measurements in the frequency domain. The efficiency of this new approach is demonstrated through experiments using an aluminum plate. The piezoelectric wafer was excited using a chirp signal and its response was analyzed using both frequency response functions (FRF) and the proposed method. The results confirm that this new approach is more sensitive to detect damage than FRF based methods. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Electromechanical impedance; Structural health monitoring; Wavelet analysis; Time-domain electromechanical impedance